Research on accurate quantification of membership of distribution terminal index based on cloud model. (September 2020) - Liao, Mengke; Xu, Hairui; Cao, Xinhui; Dong, Yuting; Zhou, Honglian; Bai, Shengli; Xing, Xiaomin
Abstract: In order to accurately assess the health status of distribution terminals, it is necessary to solve the problems of strong subjectivity and high redundancy of the index membership results in the evaluation index system. According to the empirical score given by experts, the cloud model is used to describe the actual index state and the level boundary interval respectively to form floating cloud and standard state cloud space, and the overlapping area of the two is used to represent the membership degree of the actual index. This can not only directly determine the results, but also eliminate the influence of redundant factors, and realize the accurate quantification of the index membership degree results, which widens the direction for further improving the final evaluation effect.